2021
DOI: 10.3390/molecules26082379
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Storage of Cistus ladanifer L. Bales from Mechanised Harvesting on the Essential Oil Yield and Qualitative Composition

Abstract: Cistus ladanifer is a Mediterranean native plant from which valuable products, such as essential oil, are obtained. Manual harvesting of the plants in wild shrublands is usual during short periods of time. Their mechanised harvesting could increase the volume of harvested plants and prevent fires, further storage of the plants collected being necessary. The objective of this work is to study the influence of the storage period of mechanically harvested bales on the essential oil yield and qualitative compositi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…The extraction yield of the EOs obtained by steam distillation was higher for J. communis, followed by C. sempervirens and C. ladanifer, as can be observed in Figure 1. The obtained values are within the range reported in the literature for C. ladanifer (from 0.01 to 0.63%) [20][21][22][23] while being lower for C. sempervirens for which reported yields varied from 0.20 to 0.87% [24][25][26] and higher for J. communis (reported yields from 0.05 to 0.70%) [23,[27][28][29][30]. These differences are most probably related to (i) the used samples (crown biomass that includes twigs, leaves and fruits instead of leaves or berries); (ii) the location where the plant samples were collected; (iii) the date when these samples were obtained, and (iv) the EO extraction methodology.…”
Section: Essential Oil Yieldssupporting
confidence: 87%
See 1 more Smart Citation
“…The extraction yield of the EOs obtained by steam distillation was higher for J. communis, followed by C. sempervirens and C. ladanifer, as can be observed in Figure 1. The obtained values are within the range reported in the literature for C. ladanifer (from 0.01 to 0.63%) [20][21][22][23] while being lower for C. sempervirens for which reported yields varied from 0.20 to 0.87% [24][25][26] and higher for J. communis (reported yields from 0.05 to 0.70%) [23,[27][28][29][30]. These differences are most probably related to (i) the used samples (crown biomass that includes twigs, leaves and fruits instead of leaves or berries); (ii) the location where the plant samples were collected; (iii) the date when these samples were obtained, and (iv) the EO extraction methodology.…”
Section: Essential Oil Yieldssupporting
confidence: 87%
“…Chatzopoulou and Katsiotis [34] reported that the essential oil from the leaves of J. communis from northern Greece was dominated by α-pinene (41.3%) and sabinene (17.4%) while Cabral, et al [35] and Caramiello, et al [36] identified sabinene (30.5% and 41.4%, respectively) and α-pinene (29.6% and 13.4%, respectively) as major compounds in the needle oil from J. communis species grown in Turkey and the Northwestern Italian Alps, respectively. Mediavilla, Blázquez, Ruiz and Esteban [23] found α-pinene (16-21%), sabinene (18-34%), limonene (6-8%), β-myrcene (3-5%) and β-phellandrene (3-4%) as the major compounds in samples collected in Spain in two different periods. Höferl, Stoilova, Schmidt, Wanner, Jirovetz, Trifonova, Krastev and Krastanov [16] identified α-pinene (51.4%), myrcene (8.3%), sabinene (5.8%), limonene (5.1%) and β-pinene (5.0%) as the main compounds of J. communis berries while Koukos and Papadopoulou [37] detected α-pinene (27.22-62.08%), limonene (1.31-30.96%), myrcene (5.41-20.23%), sabinene (0.35-16.47%), citronellol (5.06-15.57%), β-caryophyllene (0.79-6.61%), borneol (0.86-4.51%) and β-pinene (1.89-3.47%).…”
Section: Chemical Compositionmentioning
confidence: 93%
“…In the Mediterranean ecosystem, organic matter rapidly accumulates on the soil surface and, due to the lack of overlap between peak humidity and temperature, mineralization is extremely slow (García and Hernández, 1996;Rodeghiero et al, 2011). In addition, the high plant density of Cistus-dominated ecosystems protects the soil from direct sunlight, which generates adequate humidity for the development of these saprophytic fungi throughout the entire cycle of these very particular systems (Mediavilla et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…There are several reports describing the chemical composition of C. ladanifer essential oils from different Mediterranean countries such as Spain, [17,20] Portugal, [22,37] France [30] and Morocco, [4,24] but limited research revealing intra-and interpopulation variations is reported. [25,35] Therefore, it has already been pointed out that chemical variation occurs mainly according to geographic and genetic characteristics.…”
Section: Variations Of Essential Oil Composition Among Plots Populati...mentioning
confidence: 99%
“…From a chemical point of view, some studies have shown that α ‐pinene, viridiflorol, ( E )‐pinocarveol, p ‐cymene, camphene, bornyl acetate, and ledol are the major compounds quantified in the essential oil of C. ladanifer [4,18] . However, the published data suggest that the chemical composition of essential oil from wild‐grown C. ladanifer plants varies widely among different regions and countries [17,22–24] . In turn, Mariotti et al.…”
Section: Introductionmentioning
confidence: 99%